A thermo-economic analysis of repowering of a 250 MW coal fired power plant through integration of Molten Carbonate Fuel Cell with carbon capture. (August 2016) - Samanta, Samiran; Ghosh, Sudip
Highlights: Repowering of coal fired power plant by integrating downstream MCFC. Increase in both capacity and net efficiency due to repowering. 67% of emitted CO2 captured through repowering. Performance compared with conventional MEA-based CO2 capture technology. Lower cost of electricity (COE) compared to MEA based CO2 capture process. Abstract: This paper presents a thermo-economic assessment of a repowering configuration of a 250 MW old existing coal fired power plant through integration of Molten Carbonate Fuel Cells (MCFC) at the downstream of the existing boiler. Hydrogen-rich syngas generated from natural gas in an external reformer used as fuel in MCFC unit. In the downstream of MCFC the residual combustible species from anode side is burnt with 98% pure oxygen, followed by heat recovery, cooling and moisture separation, CO2 compression and storage. The proposed repowering scheme helps to increase the plant capacity by about 27%, while capturing 67% of emitted CO2 . Contrary to the conventional CO2 capture process, this MCFC repowering does not eat up the plant's efficiency, rather, it increases the net efficiency by 1.1%-points. The effect of repowering on cost of electricity, CO2 avoided cost (CCA), specific primary energy consumption for CO2 avoided (SPECCA) are estimated. The study shows that this repowering scheme yields a lesser unit cost of electricity (COE) compared to the commercially available monoethanolamine (MEA) based carbon capture retrofit.